Ara nesil şairi Mehmed Mahfî'nin hayatı, edebî kişiliği ve şiirleri - Çoban, Neşe (Muş Alparslan Üniversitesi, 2023)
Bu yüksek lisans tezinin amacı, hakkında müstakil bir edebî çalışma bulunamayan şair Mehmed Mahfî'nin Türk edebiyatının devirleri içerisindeki yerini belirlemek, hayatı ve edebî kişiliği ile ilgili bilgileri ortaya çıkarmaktır. Şairin şiirlerini kaleme aldığı dönemin, Ara Nesil sanatçılarının da eser verdiği 1880'li yıllara tekabül ettiği tespit edilmiştir. Bu sebeple öncelikle Ara Nesil ve bu dönemde eser veren sanatçılar hakkında çeşitli kaynaklardan bilgi edinilmiştir. Ardından ise şairin bilinen tek edebî eseri olan "Servet-i Kalb" adlı şiir kitabı incelenmiş, kitapta yer alan Arap harfli şiirler Latin harflerine aktarılmıştır. Yapılan inceleme ve araştırmalar sonucunda Ara Nesil'in edebî eğilimi ile Mehmed Mahfî'nin edebî anlayışı karşılaştırılmıştır. Bu doğrultuda Mehmed Mahfî'yi de Ara Nesil sanatçıları arasına dâhil etmek mümkündür.

The aim of this master thesis is to determine the place of the poet Mehmed Mahfî, who could not find an independent literary work, in the periods of Turkish literature, and to reveal the information about his life and literary personality. It has been determined that the years when the poet wrote his poems were the 1880s, when the artists of the Intermediate Generation also gave works. For this reason, first of all, information was obtained from various sources about the Intergenerational Period and the artists who worked in this period. Then the only literary work of poets who owned the "Servet-i Kalb (Fortune of Heart)" has examined the books of poetry, Arabic letter poems in the book of poetry were transferred to Latin alphabet. As a result of the examinations and research, the literary tendency of the Ara Nesil (Mid-Generation Period) and the literary understanding of Mehmed Mahfî were compared. Accordingly, it is possible to include Mehmed Mahfî among the Ara Nesil artists.
The mid-generation poet Mehmed Mahfî's life, literary personality and poems
Keywords: Türk Dili ve Edebiyatı; Turkish Language and Literature